Outcome of Surgery and Radiotherapy as Treatment of Early Laryngeal Cancer - Rahman, Md Mostafizur; Taous, Ahmmad; Hossain, Sheikh Mohammad Rafiqul (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Carcinoma of the larynx is the most common cancer affecting the head and neck region. Among the different stages of this disease, early cancer (T1T2N0M0) has greater possibility of cure. Its modalities of treatment are surgery and radiotherapy. Methods: The study was done to compare between outcome of surgery and radiotherapy in early carcinoma larynx T1N0 catagory only. 60 cases of early carcinoma larynx were selected purposive sampling technique from all the patients of carcinoma larynx admitted into Otolaryngology and Head-Neck Surgery Department of Bangabandhu Sheikh Mujib Medical University,Dhaka; Dhaka Medical College Hospital, Dhaka; Shaheed Suhrawardy Medical College Hospital, Dhaka; Taqwah Specialized Hospital, Dhaka from January 2010 to June 2011. Results. Study showed 16.67% of the radiotherapy group had a primary site recurrence compared with 20.0% in the surgery group at 12th months (p = 0.59) and 6.67% of those who were treated with irradiation had a recurrence in the neck. 16.67% of patients in the surgery group had a recurrence in the neck (p < 0.05). There was no significant difference in primary site recurrence rates for the two treatment modalities, but regional recurrence was higher in the surgery group. Regarding speech and voice quality, radiotherapy was far superior to surgery. All patients in the radiotherapy group but only 3 of 10 in the surgery group had good or normal voice (p = .0017). Conclusions: Both surgery and irradiation are equally effective in treating early laryngeal carcinoma but Speech and voice quality were significantly better in patients treated by radiotherapy than those treated by surgery. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 34-40